MASKULINISASI IKAN NILA (Oreochromis niloticus) MENGGUNAKAN EKSTRAK CABE JAWA (Piper retrofractum) MELALUI PERENDAMAN LARVA - Hafizhotur Rohmaniah; Denny Syaputra; Ahmad Fahrul Syarif (Journal of Aquatropica Asia, 2019)
The aimed of this study was to evaluate the effectiveness of java long pepper extract in the increasing of the percentage of males nile tilapia. The design of experiment was completely randomized design with 5 treatments i.e : A (negative control), B (1,99 mg L-1), C (3,99 mg L-1), D (5,99 mg L-1) and positive control (20 mg L-1 17α-metiltestosteron) with three replicates per level of treatment. Immersion of 10-day-old larvae for 24 hours with 50 larvae in 10 L medium of treatments and cultivated for 60 days and identification of gender using the acetocarmin method. The results showed that java long pepper extract was effective to increase the percentage of males with dose of 1,99 mg L-1 (81,78±6,81%), 3,99 mg L-1 (79,00±2,99%) and 5,99 mg L-1 (87,42±4,85%) while the negative control 39,23±7,74%. Java long pepper extract dose of 5,99 mg L-1 were not significantly different with the treatment of 17α-metiltestosteron i.e : 91,71±3,93%. Percentage of survival rate 47.33±3.06% to 53.33±8.08%, specific growth rate 3,14±0,15% to 3,40±0,08%, absolute weight growth 1.97±0.59 g to 3.07±0.38 g and absolute length growth of 3.73±0.55 cm to 3.95±0.16 cm. Java long pepper extract gives a significant effects to the spesific growth rate and absolute weight growth. Treatment A, B, C, D and E had no effect on survival rate and the absolute length growth of nile tilapia during 60 days cultivation period.